Emotional and Cognitive Factors in Shaping Entrepreneurial Competence Among Accounting Education Students - Dini Eva; Susilaningsih Susilaningsih; Asmaul Khusna (Jurnal Kewirausahaan dan Bisnis, 2026)
The increasing unemployment rate among university graduates in Indonesia—reaching 6.23% in early 2025—underscores the urgent need to strengthen entrepreneurial competence in higher education. This study examines the effect of emotional intelligence and creative thinking on entrepreneurial competence, both partially and simultaneously, among Accounting Education students at Universitas Sebelas Maret who had completed entrepreneurship coursework. Drawing on the Entrepreneurial Value Creation Theory, emotional intelligence is defined as emotional capital, and creative thinking as cognitive adaptability, both of which serve as internal entrepreneurial resources. Using a quantitative survey design with proportional stratified random sampling, data from 116 students were analyzed through multiple linear regression. The results indicate that both variables have positive and significant effects on entrepreneurial competence, individually and simultaneously, with creative thinking demonstrating stronger relative influence. These findings suggest that entrepreneurship instruction in Accounting Education programs should be redesigned to deliberately cultivate emotional and cognitive internal resources, particularly empathy and originality, as foundational competencies for future teacher-entrepreneurs.Keywords: EntreComp; entrepreneurship education; internal resources; value creation theory